Vocational education and training in in Hungary: short description - (:unkn) unknown (Publications Office of the European Union, 2024)
„This short description explores vocational education and training (VET) in Hungary within its socioeconomic context, discussing key characteristics, system developments and challenges. Hungary's VET system o ers upper secondary programmes in school-based forms, incorporating dual training, and includes various post-secondary and tertiary programmes. Labour market training programmes are designed to respond flexibly to the dynamic requirements of the labour market. This comprehensive structure provides a strong foundation of skills and key competences and fosters lifelong learning. The VET 4.0 Strategy, revised in 2023, guides Hungary's VET policy. The 2019 VET Act reshaped the system by separating VET from general education, introducing dual VET, and aligning VET with labour market demands. Partnerships between VET and higher education boost quality and excellence. Efforts continue to enhance inclusivity, career guidance, and continuous professional development for VET teachers. Social partners actively contribute to VET policy-making, ensuring the system remains adaptable to economic needs.“ (editor; BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2.2 Osteuropa; 370; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Qualifikationsentwicklung; Bildungssteuerung; Ungarn